Factors Influencing Students Intention to Choose Career of Halal Food Industry in Malaysia using Theory of Planned Behavior - Abu Bakar, Nashirah; Rosbi, Sofian; Haji Hashim, Hydzulkifli; Che Arshad, Noraziah (Inovatus Usluge Ltd., 2021)
Background: The food industry in Malaysia has experienced significant development, especially in the halal food sector. The halal food industry is a market segment involved with food items and beverages that are strictly prepared according to rules underlined by the Islamic dietary law. In addition, the concept of halal covers not only Syariah law, but also hygiene, sanitation and food safety requirements. Malaysia has become a major global halal hub in delivering halal food to local and international levels. The significant development of halal food industry in Malaysia creates significant job opportunities for new graduating students. Therefore, this study aims to evaluate factors that influence student intention to choose a career for the halal food industry in Malaysia. Research Methodology: This study using a quantitative research method with questionnaire development in assessing the factors that influence intention of students to involve in halal food industry as their future career. The underpinning theory is Theory of Planned Behavior (TPB). The independent variables are Attitude (A), Subjective Norm (SN) and Perceived Behavioral Control (PBC). This study developed four questions for each variable. Unit of analysis for respondents is university students in Malaysia. The sample size is 40 students that have an interest in working for halal food industry in Malaysia. The correlation analysis was analyzed using Pearson Correlation coefficient analysis. Meanwhile, the causal relationship was analyzed using multiple regression analysis. Results: The skewness values for four variables in this study are between -1 and +1 that indicates normal distribution. The value of Cronbach’s alpha statistical test for measuring internal reliability is larger than 0.7 for all four variables. Therefore, four constructs exhibit good reliability that indicates the suitability of internal consistency. Next, the value of R-squared for model fit in this study is 0.675 that indicates a good model fit that explained 67.5% of variance in dependent variable. Multiple regression analysis indicates Attitudes (A), Subjective Norm (SN) and Perceived Behavioral Control (PBC) are significant in predicting the value of Intention (I) to select a career in halal food industry. Conclusion: This study supported the hypothesis that indicates there is a positive and significant relationship of Attitude (A), Subjective Norm (SN) and Perceived Behavioral Control (PBC) towards Intention (I). The findings of this study add value to theoretical knowledge of career selection among university students. At the same time, this study provides guideline for government in developing better policy in cultivating interest among university students to be highly involved in the halal food industry